Greenness percentage of the said green renewable energy: A case study - Pierre Tsafack; Divine Ngwashi; Benjamin Ducharne; Emmanuel Tanyi (Energy Reports, 2019)
The manufacturing process of renewable energy components involves some conventional energy at different steps. It is then clear that the fabrication of the components of a renewable energy system will emit an amount of greenhouse gas(GHG). The work carried out in this paper is based on investigating a sample of 1m2 solar panel and analyzing the energy involved in its complete fabrication process as well as the amount of GHG emitted. The energy generated by the sample during its useful lifetime is evaluated and the prevented amount of carbon dioxide (CO2 recovered) computed; that CO2 recovered is the amount of GHG which could have been emitted if the conventional energy sources were to be used to generate that same amount of lifetime energy. The greenness percentage with regards to renewable energy material (photovoltaic) is then defined as a ratio of GHG emission (CO2-eq.) during fabrication and GHG prevented (CO2 recovered) as a result of had been using the panel throughout its entire lifetime. It appears that if manufactured in china and installed in Cameroon, the 1m2 module exhibits a greenness percentage of 49.14% in Bamenda and 29% in Ngaoundéré. The same photovoltaic sample is 98.43% green if manufactured in Cameroon and installed in China. Thus, a solar panel installed in china, if manufactured in Cameroon will need only about 0.44 years to compensate the amount of GHG emitted during manufacturing in Cameroon which is equivalent to a gain of more than 29 years of pollution free period out of the 30 years of expected average lifetime of a photovoltaic module.
Keywords: 330; Renewable energy; Carbon footprint; Conventional energy; Green energy; Greenness percentage; Lifetime; Manufacturing process; Pollution; Silicon solar cell; Sunshine